THE EFFECTIVENESS OF USING MIND MAPPING IN READING COMPREHENSION OF TENTH GRADE STUDENTS AT SMAN 10 GOWA - Elma Sumurubu; Hasnani; Suharti Siradjuddin (Kumpulan Artikel Pendidikan Anak Bangsa (Kapasa) : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The purpose of this study was to determine the effectiveness of using mind mapping on students’ reading comprehension skill. The research was a pre-experimental study wih a design using one group pre test- post test. The sample in this study was students’ of class X IPA 1 which consisted of 30 students using a random sampling technique. The result of this study showed that the mean value of the pre test was 38.50, which showed that the students’ skill in the pre test was will very low, while the mean value of the post test was 83.17, which showed that students’ reading comprehension skills had increased. The result of the data were analyzed using an independent sample- test, showing that sig, (2-tailed) was 0.00 lower than 0.05 sho that the alternative hypothesis ( Ha) was accepted and the null hypothesis (H0) was rejected. The researcher proved that it was the effectiveness of the ability to understand students’ reading through the use of mind mapping. Based on the result of this study, it can be concluded that the use of mind mapping can increase the effectiveness of reading comprehension in clas X IPA 1 students of SMA Nwgwri 10 Gowa ABSTRAK Tujuan penelitian ini adalah untuk mengetahui keefektifan penggunaan mind mapping terhadap kemampuan pemahaman membaca siswa. Penelitian ini merupakan penelitian pre- experimental dengan desain yang menggunakan one group pre test – posttest. Sample pada penelitian ini adalah siswa kelas X IPA1 yang terdiri dari 30 siswa dengan teknik random sampling. Hasil penelitian ini menunjukan bahwa pada hasil pre test nilai mean yang dimiliki adalah 38. 50 yang menunjukan yang menunjukan bahwa kemampuan siswa pada pre test masih sangat rendah sedangkan nilai mean pada posttest adalah 83. 17 yang menunjukan bahwa kemampuan memahami bacaan siswa meningkat. Hasil data dianalisis dengan menggunakan independent sample – test, menunjukan bahwa sig. ( 2- tailed ) adalah 0.00 lebih rendah dari 0.05 sehingga hipotesis alternatif ( Ha ) diterima dan hipotesis nol ( H0) ditolak. Peneliti membuktikan bahwa adalah keefektifan pada kemampuan memahami bacaan siswa melalui penggunaan mind mapping. Berdasarkan hasil penelitian ini dapat disimpulkan bawa penggunaan mind mapping dapat meningkatkan keefektifan memahami bacaan pada siswa kelas X IPA 1 SMA Negeri 10 Gowa.